Thrombin antithrombin complex and IL-18 serum levels in stroke patients - Piazza, Ornella (PAGEPress Publications, 2010)
The complex picture of inflammation and coagulation alterations comes to life in acute stroke phases. Increasing evidence points to a strong interaction and extensive crosstalk between the inflammation and coagulation systems: the interest towards this relationship has increased since recent experimental research showed that the early administration of antithrombin III (ATIII) decreases the volume of ischemia in mice and might be neuroprotective, playing an antiinflammatory role. We aimed to establish the extent of the relationship among markers of inflammation (S100B and IL-18) and procoagulant and fibrinolytic markers (ATIII, thrombin-antithrombin III complex (TAT), Fibrin Degradation Products (FDP), D-dimer) in 13 comatose patients affected by focal cerebral ischemia. Plasma levels of TAT, D-dimer and FDP, IL18 and S100B were increased. IL-18 and S100B high serum levels in ischemic patients suggest an early activation of the inflammatory cascade in acute ischemic injury. The basic principles of the interaction between inflammatory and coagulation systems are revised, from the perspective that simultaneous modulation of both coagulation and inflammation, rather than specific therapies aimed at one of these systems could be more successful in stroke therapy.